Factor associated with and risk of cardiovascular disease in people with uncontrolled hypertension - Sara Ringwald-de Meyer; Roxane de La Harpe; Peter Vollenweider; Pedro Marques-Vidal; Julien Vaucher (Scientific Reports)
Abstract We aimed to identify and validate factors related to uncontrolled hypertension. Participants treated with at least one antihypertensive drug from the prospective contemporaneous CoLaus|PsyCoLaus study were enrolled. We investigated the association between hypertension status (uncontrolled, defined as systolic blood pressure [SBP] ≥ 140 mm Hg and/or diastolic blood pressure [DBP] ≥ 90 mm Hg, versus controlled hypertension [SBP/DBP < 140/90 mm Hg]) and potential risk factors. Additionally, the prospective association of uncontrolled hypertension with cardiovascular disease and all-cause mortality was evaluated. 1040 participants recruited between 2003 and 2006 with a mean follow-up of 12.3 years (SD ± 3.4) were included in the analyses. Heavy alcohol consumption, increased BMI, increased ferritin and albuminuria were positively associated with uncontrolled hypertension. Factors inversely associated with uncontrolled hypertension were university degree, current smoker, and high potassium urinary excretion. Uncontrolled hypertension status was not associated with incident ASCVD nor all-cause mortality in our study. In conclusion, uncontrolled hypertension was associated with modifiable factors, such as heavy drinking, obesity and level of education. Further studies should investigate whether including biological markers in clinical practice, such as potassium excretion, ferritin levels, or albuminuria, would help identify individuals who may develop uncontrolled hypertension.